Laparoscopic adrenalectomy for metastatic adrenal tumor. Issue 1 (20th November 2013) - Hirayama, Takahiro; Fujita, Tetsuo; Koguchi, Dai; Nishi, Morihiro; Kurosaka, Shinji; Tsumura, Hideyasu; Tabata, Ken‐ichi; Iwamura, Masatsugu
Abstract Introduction Treating adrenal metastases from primary malignancies with laparoscopic adrenalectomy (LA) remains controversial. The aim of this study was to evaluate the feasibility, effectiveness and efficiency of LA for solitary adrenal metastasis. Methods From November 2003 to September 2012, eight consecutive patients with adrenal metastasis were treated with LA. A retrospective study was conducted, and clinical and histological data were analyzed. Results All LA were successfully performed. There were no major complications, blood transfusions or conversions to open adrenalectomy. The patients included seven men and one woman with a median age of 59 years at the time of operation. Adrenal metastases were most commonly noted to be from non‐small‐cell lung cancer (four patients) and renal cell carcinoma (four patients). The majority of adrenal metastases were unilateral (right: one patient; left: seven patients). One patient had bilateral metastases. The median overall survival was 14 months. Four patients (two with non‐small‐cell lung cancer; two with renal cell carcinoma) were alive with no evidence of metastatic disease as of October 2013. Conclusion LA is a safe and effective procedure for patients with isolated metastases. Surgical resection with LA for a solitary adrenal metastasis from primary malignancy can achieve a good prognosis.